A new shallow-water mud crab of the genus Hexapanopeus Rathbun, 1898 from Belize (Crustacea: Decapoda: Panopeidae) - Felder, Darryl L.; Thoma, Brent P. (Zootaxa, 2022)
A new species of panopeid crab from shallow coastal waters of Belize is formally described and named based upon comparative study of three small specimens obtained in the course of a regional biodiversity survey of decapod crustaceans. The herein designated holotype of Hexapanopeus klausruetzleri n. sp. is a specimen previously included in a comparative molecular phylogenetic analysis that showed it to be closely related to, but genetically distinct from, the western Atlantic species Hexapanopeus angustifrons (Benedict & Rathbun, 1891). Hexapanopeus klausruetzleri n. sp. differs from this widely reported warm-temperate species in both its smoother carapace and pereopod surfaces and its generally more lobiform anterolateral teeth. The unique male first gonopod of the new species also strongly supports its morphological separation from all known congeners and other superficially similar western Atlantic panopeids with which it might be confused. To date, mature females have not been found, and the limited available collections are restricted to the vicinity of Carrie Bow Cay and nearby waters. Fourteen additional species of small panopeid and pseudorhombilid crabs, similar to Hexapanopeus klausruetzleri n. sp. in size and general habitus, were taken in the course of our studies in Belize. Most have not been previously reported from these waters, and several warrant further study to confirm their identifications.